The Arabidopsis thalianaCONSTANS-LIKE 4 (COL4) – A Modulator of Flowering Time - Steinbach, Yvonne (Frontiers in Plant Science, 2019)
Appropriate control of flowering time is crucial for crop yield and the reproductive success of plants. Flowering can be induced by a number of molecular pathways that respond to internal and external signals. In Arabidopsis, expression of the key florigenic signal FLOWERING LOCUS T (FT) is positively regulated by CONSTANS (CO) a BBX protein sharing high sequence similarity with 16 CO-like proteins. Within this study, we investigated the role of the Arabidopsis CONSTANS-LIKE 4 (COL4), whose role in flowering control was unknown. We demonstrate that, unlike CO, COL4 is a flowering repressor in long days (LD) and short days (SD) and acts on the expression of FT and FT-like genes as well as on SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1). Reduction of COL4 expression level leads to an increase of FT and APETALA 1 (AP1) expression and to accelerated flowering, while the increase of COL4 expression causes a flowering delay. Further, the observed co-localization of COL4 protein and CO in nuclear speckles supports the idea that the two act as an antagonistic pair of transcription factors. This interaction may serve the fine-tuning of flowering time control and other light dependent plant developmental processes.